Partial deletions are associated with an increased risk of complete deletion in AZFc: a new insight into the role of partial AZFc deletions in male infertility - Zhang, Feng (BMJ Group, 2007)
BACKGROUND: The AZFc region on the human Y chromosome has been found to be functionally important in spermatogenesis. Complete AZFc deletion is one of the most frequent causes of male infertility and the roles of partial AZFc deletions (gr/gr and b2/b3 deletions) in spermatogenesis are controversial. METHODS: To further study the roles of partial AZFc deletions in spermatogenic impairment and the relationship between complete and partial AZFc deletions, these deletions were typed and quantitative analysis of DAZ gene copies and Y chromosome haplogrouping were performed for seven pedigrees of complete AZFc deletion carriers, comprising 296 infertile and 280 healthy Chinese men. RESULTS: Neither the gr/gr nor the b2/b3 deletion was found to be associated with spermatogenic failure. In one pedigree, a complete AZFc deletion was observed to result from the gr/gr deletion, suggesting that complete deletions of AZFc can be preceded by partial deletions. In addition, a new gr/gr‐deleted Y haplogroup Q1 was identified and the reported fixation of the b2/b3 deletion in haplogroup N confirmed. The frequency of complete AZFc deletion in haplogroups Q1 and N was significantly higher than that in the other haplogroupsm with fewer partial deletions. Duplications of DAZ gene copies were also observed in this study. CONCLUSIONS: To date, these observations comprise the first evidence showing that partial AZFc deletions can increase the risk of complete AZFc deletion. The susceptibility of partial AZFc deletions to complete AZFc deletion deserves further examination, especially in the populations or Y haplogroups abundant in partial AZFc deletions.